2014
DOI: 10.1103/physrevb.90.064430
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Ising magnetic behavior of itinerant spin-polarized carriers inURu2Si2

Abstract: We show on the basis of electronic structure calculations that the uranium 5f magnetic moment in URu2Si2 exhibits a unique Ising behavior, which surprisingly, arises from itinerant electronic states. The origin of the unusual Ising behavior is analyzed as due to the peculiar near-Fermi edge nested electronic structure of URu2Si2 involving its strong spin-orbit interaction. The Ising anisotropy has pertinent implications for theories applicable to explaining the Hidden Order phase in URu2Si2. PACS numbers: 71.2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…To predict the most likely multipoles, ab initio electronic structure calculations of URu 2 Si 2 in the nonmagnetic and AFM phases have been performed. 160,318,361,[371][372][373] These calculations notably correctly reproduce many of the known properties of URu 2 Si 2 , as e.g.…”
Section: /67supporting
confidence: 54%
“…To predict the most likely multipoles, ab initio electronic structure calculations of URu 2 Si 2 in the nonmagnetic and AFM phases have been performed. 160,318,361,[371][372][373] These calculations notably correctly reproduce many of the known properties of URu 2 Si 2 , as e.g.…”
Section: /67supporting
confidence: 54%
“…A relativistic DFT calculation predicted an Ising behavior for the band-like 5f electrons in URu 2 Si 2 with magnetic moments along the c axis and no anisotropy in the basal plane. 22,91 Here, the 5f electrons are treated as fully itinerant and the calculation is performed for the antiferromagnetic phase which has practically the same Fermi surface than the hidden order state. 29,[43][44][45] This is justified as the Fermi surfaces for the localized 5f 2 or for the localized 5f 3 uranium configuration are not in correspondence to the experimentally observed ones.…”
Section: B Anisotropy Of the G-factormentioning
confidence: 99%
“…21 The strong Ising character of the 5f electrons in URu 2 Si 2 has been also confirmed on the basis of density functional theory (DFT) electronic structure calculations. 22 The Ising anisotropy arises from a combination of the peculiar Fermi surface nesting and strong spin-orbit interaction. While in this electronic structure calculations the 5f electrons are treated fully itinerant, other models supposing a localized 5f 2 non-Kramers doublet ground state could explain the large magnetic uniaxial anisotropy as well.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario of a localised CEF doublet explains the Ising behaviour, but for other CEF schemes, e.g., the two CEF singlets invoking hexadecapolar order [63,67], Ising anisotropy is unproven. Surprisingly recent relativistic DFT calculations [97] showed that the bandlike 5f electrons in URu 2 Si 2 exhibit a colossal Ising behaviour, a property which is truly exceptional for itinerant electrons. In Fig.…”
Section: Localizes Vs Itinerant Description Of Ising Anisotropymentioning
confidence: 99%